2006
DOI: 10.1038/sj.hdy.6800880
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of genetic diversity across European subspecies of the mountain hare, Lepus timidus L.

Abstract: Fossil evidence shows that populations of species that currently inhabit arctic and boreal regions were not isolated in refugia during glacial periods, but instead maintained populations across large areas of central Europe. These species commonly display little reduction in genetic diversity in northern areas of their range, in contrast to many temperate species. The mountain hare currently inhabits both temperate and arctic-boreal regions. We used nuclear microsatellite and mtDNA sequence data to examine pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
(58 reference statements)
3
33
0
1
Order By: Relevance
“…There are five extant European mountain hare subspecies differentiated by morphophysiological characteristics, behaviour, and ecology (Angerbjörn and Flux 1995). There is generally low genetic differentiation between subspecies, indicative of a post-glacial panmictic European population, which subsequently underwent fragmentation, isolation, and divergence (Hamill et al 2006). The most widespread subspecies, recognised as the typical form (and thus presumed similar to the ancestral type), is the northern hare (L. timidus timidus, Linnaeus 1758) which inhabits tundra (in the north) and boreal forest (further south) in the Arctic and Fennoscandia (Angerbjörn and Flux 1995).…”
Section: Introductionmentioning
confidence: 99%
“…There are five extant European mountain hare subspecies differentiated by morphophysiological characteristics, behaviour, and ecology (Angerbjörn and Flux 1995). There is generally low genetic differentiation between subspecies, indicative of a post-glacial panmictic European population, which subsequently underwent fragmentation, isolation, and divergence (Hamill et al 2006). The most widespread subspecies, recognised as the typical form (and thus presumed similar to the ancestral type), is the northern hare (L. timidus timidus, Linnaeus 1758) which inhabits tundra (in the north) and boreal forest (further south) in the Arctic and Fennoscandia (Angerbjörn and Flux 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, a high divergence between British and Irish populations has been found in certain species. For example, Hamill et al (2006) found that populations of mountain hares (L. timidus) in Scotland and Ireland belonged to different mitochondrial DNA (mtDNA) clades and showed high divergence based on nuclear microsatellite data, reporting F ST values above 0.4.…”
Section: Introductionmentioning
confidence: 99%
“…As the "random histories" failed to provide a clear picture of the demographic history of L. The statistical power for the models of the "old-change test" was moderate but rose to high 430 levels when a Bayes factor of 2.0 was used as a threshold criterion (Table S6) (Hamill et al, 2006;Suchentrunk et al, 1999). However, the historically high 461 levels of diversity revealed in our analyses suggest that the mountain hare has maintained 462 diversity over time unlike many classic arctic/alpine specialists.…”
mentioning
confidence: 99%